2012
DOI: 10.1371/journal.pone.0033080
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella Type III Secretion Hyper-Activity Which Results in Biofilm-Like Cell Aggregation

Abstract: We have previously reported the cloning of the Salmonella enterica serovar Typhimurium SPI-1 secretion system and the use of this clone to functionally complement a ΔSPI-1 strain for type III secretion activity. In the current study, we discovered that S. Typhimurium cultures containing cloned SPI-1 display an adherent biofilm and cell clumps in the media. This phenotype was associated with hyper-expression of SPI-1 type III secretion functions. The biofilm and cell clumps were associated with copious amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 59 publications
2
26
0
1
Order By: Relevance
“…The increasing expression levels were observed for invA and sipB-C (Fig. 3) were similar to the findings of Xu, Lee, and Ahn (2010), and the secreted SPI-1 protein substrates spB, sipC and sipA are also shown to offer a special contribution to biofilm development by cell clumping through recruitment of non-attached cells into the adherent cell community (Jennings et al, 2012). On the contrary, relative expression levels of the genes tested in biofilm cells were inhibited when cells were grown in MTLB; especially at 7 days (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increasing expression levels were observed for invA and sipB-C (Fig. 3) were similar to the findings of Xu, Lee, and Ahn (2010), and the secreted SPI-1 protein substrates spB, sipC and sipA are also shown to offer a special contribution to biofilm development by cell clumping through recruitment of non-attached cells into the adherent cell community (Jennings et al, 2012). On the contrary, relative expression levels of the genes tested in biofilm cells were inhibited when cells were grown in MTLB; especially at 7 days (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Attachment genes involving adrA, bapA, csgD, csrA and rpoS could be indispensable for initial attachment or biofilm maturation as they promote cellecell interactions (Steenackers, Hermans, Vanderleyden, & De Keersmaecker, 2012), genes of sdiA and luxS associated with quorum sensing networks were thought to play a role in the production of healthy and fully developed biofilm (Bai & Rai, 2011). It was shown that genes of invA, sipB and sipC involved in Salmonella type III secretion may be association with the cell aggregates and mediate biofilm formation (Jennings et al, 2012). However, so far, few study has focused on the expression of these genes during biofilm formation of food-borne Salmonella grown in food substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological relevance of this host-independent secretion remains to be explored. Interestingly, it has been recently shown that S. enterica serovar Typhimurium overexpressing SPI1 displays an adherent biofilm that is able to massively recruit heterologous nonbiofilm forming bacteria [160]. Although this phenotype is not observed when SPI1 is expressed from its original genomic location, the authors suggest a number of potential uses for engineered biofilm formation including bioremediation, biofuel cell design, and engineered infections for beneficial purposes.…”
Section: Extracellular Roles and Applications Of Effectors T3ss1mentioning
confidence: 99%
“…However, the fact that we were able to complement the mutant phenotype with prgH alone and not the whole operon suggests that prgIJK are expressed normally in the prgH mutant (⌬prgH::Cm r ) and there is no polar effect or that these other genes have no effect on the persistence of the pathogen in this vector. Besides a role in host invasion, S. enterica SPI-1 has also been associated with bacterial adhesion and clumping in media, which demonstrated the possibility of T3SS-mediated bacterial aggregation outside eukaryotic host cells (49). Induction of prgH expression was observed in the mid-and hindgut of M. quadrilineatus for up to 48 h post-AAP, and the prgH mutant had low retention during gut passage and persistence postacquisition compared to the WT.…”
Section: Discussionmentioning
confidence: 99%